(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this particular paper we provide a novel contribution to the source curse literature. We provide an empirical and theoretical analysis to build that all-natural resources represent per se an optimistic element for nation’s economic development, but tend to result in really unequal cash flow distribution within nations on account of the internal characteristic of theirs of being readily appropriable. We anticipate hypothetically the gap between households having a chance to access natural resources and those not having access to natural sources gets a lot more marked when raw natural sources are exclusively exported as well as don’t stand for an intermediate feedback for domestic manufacturing. The empirical results of ours suggest that this’s especially the case for ores and metals.